PENGEMBANGAN TECHNOPRENEURSHIP DI UNIVERSITAS RIAU - Sumarno Sumarno; Saryono Saryono; Gimin Gimin (PROMOSI: Jurnal Program Studi Pendidikan Ekonomi, 2017)
Nation or state will prosper if it have at least 2% of entrepreneurs.According to the Minister of Cooperatives and SMEs, entrepreneurs in Indonesia are still around 1.6%.For that, we need to developtechnopreneurship in order to produce highly competitive entrepreneurs.The purpose of this research is to get information about technopreneurship development in University of Riau.The research was conducted on the application of entrepreneurship at University of Riau, Pekanbaru.Data were collected through interviews, observation, and documentation, analyzed descriptively.The results showed that the number of students who have a business plan in accordance with their academic disciplines on average only 5%.The factor is the implementation of technopreneurship development has not been optimal.Lecturers have not emphasized the creative ability of students in accordance with academic science, while entrepreneurship lecturers only instill knowledge, insight, and entrepreneurial interest.Units and support student entrepreneurship programs have not direct students' creative business ideas to the field that were appropriate to their academic sciences.